The rogerian approach as a possibility of intervention, prevention and combating bullying - Rone Aparecido Dias Barbosa; Bruna Paes de Barros (Universidade Estadual Paulista Júlio de Mesquita Filho, 2016)
Bullying is a phenomenon that happens in schools and it became evident especially in recent decades. How the professionals working in education deal with interpersonal relationships in the school environment can be decisive in preventing and combating this phenomenon, which can cause major consequences for those involved in its occurrence. In this sense, Carl Ransom Rogers published articles and books dealing with the facilitation of relationships between teachers and students for personal development, a matter which, in this study, will seize to relate to bullying. The objective of this work is to collaborate with the humanities on the theme growing about bullying from the perspective of Humanistic Psychology. We performed a literature search on this topic in journals, books and scientific databases PePSIC, SciELO and BVS-Psi Brasil. The person-centered approach and other derived formulations of such an approach, such as student-centered learning and humanistic conciliation are the main findings, which aim to promote the facilitation of interpersonal relationships and, thus, are characterized as important tools to be used by teachers and allied professionals to prevent and combat bullying.